2014
DOI: 10.1007/s11356-014-2568-6
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the antibacterial effects of silver-modified TiO2 and ZnO plasmonic photocatalysts embedded in polymer thin films

Abstract: Nanosilver-modified TiO2 and ZnO photocatalysts were studied against methicillin-resistant Staphylococcus aureus on the surface and against naturally occurring airborne microorganisms. The photocatalysts/polymer nanohybrid films were prepared by spray coating technique on the surface of glass plates and on the inner surface of the reactive light source. The photoreactive surfaces were activated with visible light emitting LED light at λ = 405 nm. The optical properties of the prepared photocatalyst/polymer nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
47
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 54 publications
4
47
0
Order By: Relevance
“…) Moreover, it was also presented that the obtained hybrid layer shows improved photocatalytic and antibacterial properties because the biocompatible and HAp microlamellae are potential candidates as support materials for the attached P25 TiO 2 photocatalyst NPs 18 . Functional surfaces with photocatalyst content can kill numerous microorganisms because of its photocatalytic properties and the strong photocatalytic activity of this hybrid thin films are reported in the literature 17,19,20,21 . Due to the appearance of reactive radicals, the photocatalyst particles can degrade many organic compounds and inactivate microorganisms via destroying the cell wall and their DNA, respectively.…”
Section: áBra Az éRdes Felülettel Rendelkezõ Réteges-kettõs Oxid (Ldmentioning
confidence: 96%
See 1 more Smart Citation
“…) Moreover, it was also presented that the obtained hybrid layer shows improved photocatalytic and antibacterial properties because the biocompatible and HAp microlamellae are potential candidates as support materials for the attached P25 TiO 2 photocatalyst NPs 18 . Functional surfaces with photocatalyst content can kill numerous microorganisms because of its photocatalytic properties and the strong photocatalytic activity of this hybrid thin films are reported in the literature 17,19,20,21 . Due to the appearance of reactive radicals, the photocatalyst particles can degrade many organic compounds and inactivate microorganisms via destroying the cell wall and their DNA, respectively.…”
Section: áBra Az éRdes Felülettel Rendelkezõ Réteges-kettõs Oxid (Ldmentioning
confidence: 96%
“…4. ) 20 . The developed nanohybrid films have antibacterial properties even against Enterococcus faecalis (Fig.…”
Section: áBra Az éRdes Felülettel Rendelkezõ Réteges-kettõs Oxid (Ldmentioning
confidence: 99%
“…We studied two newly developed photocatalysts/polymer nanohybrid films: TiO 2copolymer and Ag-TiO 2 -copolymer containing 0.001% silver nanoparticles. Both were applied with the spray coating technique, and activated with LED light (λ = 405 nm).The photocatalytic antibacterial activity of TiO 2 and Ag-TiO 2 coatings was established previously, and it was found that the role of photocatalytic activity was dominant over the antibacterial effect of silver ions themselves 25 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 primary epithelial cells showed higher sensitivity than immortalized cell lines to inflammatory cytokines 27 . Endosseus dental implants are placed into the alveolar bone, but the transgingival parts are surrounded by soft tissues.…”
mentioning
confidence: 99%
“…39,41,43,61,62,[87][88][89][90][91] By combining several materials, different groups have developed antibacterial coatings that are anticorrosive, 39,43 titanium dioxide has also been combined with both silver nanoparticles and zinc oxide (ZnO) to improve the broad-spectrum antibacterial coverage of the coating. 61,62 Selvam et al demonstrated that the ZnO in these coatings performed better against both S. aureus and E. coli than the TiO 2 and silver nanoparticles alone. 61 It is hypothesized that the ZnO enhances the antibacterial activity because it readily permeates bacterial membranes through the generation of hydrogen peroxide.…”
mentioning
confidence: 99%
“…61 It is hypothesized that the ZnO enhances the antibacterial activity because it readily permeates bacterial membranes through the generation of hydrogen peroxide. 62 Furthermore, TiO 2 has been combined with copper to form antifungal coatings on titanium. 88 Summary.…”
mentioning
confidence: 99%